Thermodynamics on compositional design of slag for the Ti content control in bearing steel - Pengzhao Zhang; Guangqiang Li; Chengyi Zhu; Zhicheng Zhang; Yu Liu (Journal of Materials Research and Technology, 2023)
The control of low Ti content is vital to reducing the adverse effects of TiN inclusions on fatigue life of bearing steel. Compared with the strict Ti content control of raw materials, the Ti content control by interaction between refining slag and bearing steel costs less. The effect of interaction between slag and steel on the Ti content of bearing steel was explored by equilibrium tests and the thermodynamic calculation based on the ion and molecule coexistence theory. The results show that the driving force for the reaction of the Ti and Al in steel and the SiO2 in slag increases with the decrease of the slag basicity, but the driving force for the reduction of TiO2 in slag by Al in steel also increases. Therefore, low Ti content in bearing steel can be obtained by appropriately reducing the basicity and TiO2 content of refining slag and Al content in steel, and properly increasing the Al2O3 content in the slag. For the compositional design of CaO–SiO2–Al2O3-0.1wt%TiO2-1wt%MgO refining slag used for low Ti bearing steel, the slag basicity should be less than 2 and Al2O3 content is 30–50%, or the slag basicity is 3 and Al2O3 content is decreased to 30-40wt%.